Selectivity tailoring in liquid phase oxidation over MWNT-Mn3O4 nanocomposite catalysts - Biswal, Mandakini; Dhas, Vivek V.; Mate, Vivek R.; Banerjee, Abhik; Pachfule, Pradip; Agrawal, Kanika L.; Ogale, Satishchandra B.; Rode, Chandrashekhar V. (Journal of Physical Chemistry C, 2011)
Highly selective multiwalled nanotubes (MWNT)-Mn3O4 nano-composite catalyst was designed for liquid phase oxidation of p-cresol, which gave highest selectivity of 90% to the first step oxidation product, p-hydroxy benzyl alcohol. Mn3O4 nanoparticles and MWNT-Mn3O4 nanocomposites were synthesized by coprecipitation route using mixed precursors under controlled conditions. The phase purity of Mn3O4 and the formation of MWNT-Mn3O4 nanocomposites were confirmed by X-ray diffraction, Raman spectroscopy, and X-ray photoelectron spectroscopy. High-resolution transmission electron microscopy revealed the selective exposure of (101) and (001) planes of Mn3O4 nanoparticles in the MWNT-Mn3O4 composite, while lowering in oxidizing capacity of MWNT-Mn3O4 nanocomposite confirmed by cyclic voltametry was due to incorporation of electron rich MWNT. Thus, selectivity tuning of the new material (MWNT-Mn3O4 nanocomposite) was found to be due to alteration in both geometric as well as electronic properties. A plausible reaction pathway also has been proposed involving the predominant role of nucleophilic lattice oxygen (O2-) species due to exposure of particular crystal planes giving highest selectivity to p-hydroxy benzyl alcohol.

Shape preserving chemical transformation of ZnO mesostructures into anatase TiO2 mesostructures for optoelectronic applications - Muduli, Subas; Game, Onkar S.; Dhas, Vivek V.; Yengantiwar, Ashish; Ogale, Satishchandra B. (Energy & Environmental Science, 2011)
In this work we report on the synthesis of various ZnO mesostructures (rods, spheres, flakes and flower-like morphologies) by hydrothermal and co-precipitation methods and their remarkable and complete transformation into anatase TiO2 mesostructures with nominally similar shapes using controlled low temperature TiCl4 treatment. Various techniques are used to demonstrate the phase purity and morphology details. Based on the careful examination of the transformation of ZnO rods into TiO2 tubes we suggest a mechanism which embodies initial formation of a thin TiO2 shell on the ZnO surface by ion exchange (Ti4+-Zn2+) followed by Zn diffusion through the shell and its oxidation on the surface. We used these converted TiO2 mesostructures for light harvesting in Dye Sensitized Solar Cells (DSSCs) to enhance the conversion efficiency. It is shown that DSSCs made using a doctor bladed film of TiO2 nanoparticles with an overlayer of TiCl4 treated ZnO flowers yield a solar cell efficiency of 6.9% which is considerably higher than that with only TiO2 nanoparticle film (5.4%) of comparable thickness.